What to Do When Everyone Wants You to Collaborate: Managing the Demand for Library Support in Systematic Review Searching - Sandy Campbell; Marlene Dorgan (Journal of the Canadian Health Libraries Association, 2015)
The demand for systematic review support in academic health sciences libraries is increasing. To manage the demand, the John W. Scott Health Sciences Library at the University of Alberta has created an action plan consisting of eight strategies. The results of implementing these strategies have been varied. Some have shown immediate results, while others are long term strategies.